Intrinsic Motivation to Learn: The Nexus Between Psychological Health and Academic Success - Froiland, John Mark; Oros, Emily; Smith, Liana; Hirchert, Tyrell (California school psychologist, 2012)
Intrinsic motivation (IM) to learn, if cultivated, can lead to many academic and social/emotional improvements among K-12 students. This article discusses intrinsic motivation to learn as it relates to Self Determination Theory and the trouble with relying solely on extrinsic motivators. The academic benefits of IM in the specific subject areas of reading and mathematics are reviewed, as well as various psychological benefits (e.g., enhanced persistence, prosocial behavior and happiness). Science-based methods of fostering IM in students are considered, especially enhancing children’s environments through elevating teacher and parental autonomy support. Suggestions for integrating intrinsic motivation with behavioral interventions are also provided.